2018
DOI: 10.1002/nbm.4050
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying cardiac‐induced brain tissue expansion using DENSE

Abstract: Brain tissue undergoes viscoelastic deformation and volumetric strain as it expands over the cardiac cycle due to blood volume changes within the underlying microvasculature. Volumetric strain measurements may therefore provide insights into small vessel function and tissue viscoelastic properties. Displacement encoding via stimulated echoes (DENSE) is an MRI technique that can quantify the submillimetre displacements associated with brain tissue motion. Despite previous studies reporting brain tissue displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…This error represents between 2.4%‐4% of the maximum cardiac displacement (cardiac displacement has been reported to be between 6‐10 mm 30 ). Although this displacement error (240 µm) is acceptable for cardiac displacement, it is higher than the maximum average displacement reported for healthy brain tissue (100‐187 µm) 12,13 . In this study, we compared the displacement from DENSE to that of LDV in 4 locations on the moving plate with peak displacement ranging from 1.04 mm to 0.22 mm.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This error represents between 2.4%‐4% of the maximum cardiac displacement (cardiac displacement has been reported to be between 6‐10 mm 30 ). Although this displacement error (240 µm) is acceptable for cardiac displacement, it is higher than the maximum average displacement reported for healthy brain tissue (100‐187 µm) 12,13 . In this study, we compared the displacement from DENSE to that of LDV in 4 locations on the moving plate with peak displacement ranging from 1.04 mm to 0.22 mm.…”
Section: Discussionmentioning
confidence: 95%
“…Although this displacement error (240 µm) is acceptable for cardiac displacement, it is higher than the maximum average displacement reported for healthy brain tissue (100-187 µm). 12,13 In this study, we compared the displacement from DENSE to that of LDV in 4 locations on the moving plate with peak displacement ranging from 1.04 mm to 0.22 mm. Peak displacements of 1.04 mm and 0.22 mm represent in vivo brain tissue displacement reported for pathological 34 and healthy subjects 12 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent development of movement-based imaging modalities such as DENSE-MRI ( Aletras et al , 1999 ; Adams et al , 2019 ) and amplified magnetic resonance imaging (aMRI) has shown promising results for studying the complex motions of the brain, based on physiological dynamics ( Holdsworth et al , 2016 ; Terem et al , 2018 ). aMRI uses the periodic cardiac-induced blood pulsation as a loading force to visualize and quantify sub-voxel displacement of brain tissues.…”
Section: Introductionmentioning
confidence: 99%